2020
DOI: 10.1016/j.nicl.2020.102355
|View full text |Cite
|
Sign up to set email alerts
|

Fixel-based analysis reveals fiber-specific alterations during the progression of Parkinson’s disease

Abstract: Highlights Brain network dysfunction is the core mechanism of Parkinson’s disease. Fixel-based analysis is a novel method to detect fiber-specific white matter alterations. Degeneration of corpus callosum fiber density was related to the motor symptoms. Increased cortical spinal tract fiber density may compensate the motor impairments in Parkinson’s disease. Fiber alterations were different across disease stages of Par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
35
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 70 publications
3
35
1
Order By: Relevance
“…The same trend is replicated in the elevated FA and decreased MD in the same hemisphere from VBA Study 1 . These results confirmed the observation in a few previous studies (Li et al ., 2020; Mole et al ., 2016), where higher FD and FA in CST were detected in PD compared to HC. However, while these studies suggested bilateral changes, we observed primarily unilateral alterations, potentially due to the consideration of symptom laterality onset.…”
Section: Discussionsupporting
confidence: 94%
See 4 more Smart Citations
“…The same trend is replicated in the elevated FA and decreased MD in the same hemisphere from VBA Study 1 . These results confirmed the observation in a few previous studies (Li et al ., 2020; Mole et al ., 2016), where higher FD and FA in CST were detected in PD compared to HC. However, while these studies suggested bilateral changes, we observed primarily unilateral alterations, potentially due to the consideration of symptom laterality onset.…”
Section: Discussionsupporting
confidence: 94%
“…In common with the existing FBA studies on PD progression (Li et al ., 2020; Rau et al ., 2019; Zarkali et al ., 2020), both of which used 3T data, we have identified the splenium of CC, CST, SCP, cingulum, and fornix as regions that are affected by the disease. However, within these tracts, the specific trends in fixel-based measures don’t always agree among previous studies (Li et al ., 2020; Rau et al ., 2019) and ours. For example, Rau et al .…”
Section: Discussionmentioning
confidence: 65%
See 3 more Smart Citations